Molecular characterisation of extended-spectrum beta-lactamase- and carbapenemase- producing Pseudomonas aeruginosa from a tertiary hospital in Malaysia / Hannah Phoon Yik Phing - Hannah Phoon , Yik Phing (2018)
Pseudomonas aeruginosa infections are responsible for high morbidity and mortality rates globally. Increasing resistance towards β-lactams, especially carbapenems pose a serious therapeutic challenge. However, the multilocus sequence typing (MLST) of extended-spectrum beta lactamase (ESBL)- and carbapenemase-producing clinical P. aeruginosa have not been reported in Malaysia. In addition, few studies in Malaysia reported characterisation of P. aeruginosa from hospital environmental sources. The objectives of this study were to determine the antibiotic susceptibility profiles, resistance genes, pulsotypes and sequence types of clinical and environmental P. aeruginosa from a tertiary hospital in Malaysia. These characteristics were analysed by disk diffusion, minimum inhibitory concentration, PCR, pulsed-field gel electrophoresis (PFGE), and MLST for 199 non-replicate clinical strains and 29 environmental strains. The 29 environmental strains were isolated from a total of 358 swab and fluid samples from healthcare workers’ hands, frequently touched surfaces, medical equipment, patients’ immediate surroundings, ward sinks and toilets and solutions or fluids of 12 selected wards. Less than 90% of the 199 clinical strains were susceptible towards the carbapenems and piperacillin-tazobactam, whilst ≥ 90% of the strains remained susceptible to all other classes of antimicrobial agents tested. All 29 environmental strains were susceptible to antibiotics tested. The 12 multidrug resistant strains displayed high level resistance to cephalosporins (48 to ≥ 256mg/L), and carbapenems (4 to 32 mg/L). Eleven clinical strains harboured the class 1 integron containing blaGES-13, blaVIM-2, blaVIM-6, blaOXA-10, aacA(6’)-Ib, aacA(6’)-II, aadA6 and gcuD gene cassettes. The extra-integron genes, blaGES-20, blaIMP-4, blaVIM-2, and blaVIM-11 were also found. The top three sources of clinical strains were sputum (25.6%), wound swab (16.6%), and tracheal aspirate (15.6%); the majority of which were isolated from patients in the medical wards (30.2%), surgical wards (16.6%), and the ICU (13.6%). Distribution of the environmental P. aeruginosa were mostly from moist and semi aqueous environments of handwashing sinks and toilets. The PFGE method subtyped the strains from the NICU into two major clusters and this finding agreed with the MLST data. This implies that there was an undetected outbreak of antibiotic susceptible P. aeruginosa clones at the time of sampling. Based on the PFGE analysis, strains were shown to be genetically heterogeneous with multiple subtypes of P. aeruginosa persisting in the different locations or wards in the hospital. The investigation of the genetic linkage for drug resistant international lineages is better mapped via MLST. The STs 235, 809, and 1076 clonal clusters consisted of MDRPA clinical strains. P. aeruginosa ST111 and ST235 strains were previously reported to be multidrug or extensively-drug resistant high-risk international clones found in France, Germany, Japan, Spain and Belgium. Overall, the Maximum Likelihood (ML) tree showed concordance in the clustering of clinical and environmental strains having the same STs, and PFGE clusters implying that both subtyping methods are useful for the investigation of the genetic relatedness P. aeruginosa lineages. This is the first report of the blaGES-13 and blaGES-20 ESBL-encoding gene variants and novel sequence types (STs 2329, 2335, 2337, 2338, 2339, 2340, and 2341) of P. aeruginosa in Malaysia.